PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (TELAAH TERHADAP UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM) - Widyarini Indriasti Wardani (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
The regulation of land procurement for development in the public interest has established since the Dutch colonial administration. Its laws and regulationsundergo many changes based on the government political laws in the land sector. Law Number2 of 2012 on land procurement for development in the public interest has accommodated various public interests among others included several principles of public interest objectives to minimize any conflicts which caused by the decision to take citizens' rights ofland for public use. Other thingswhichregulated are the Implementation of Land Procurement by Land Agency (BPN), Determination of Compensation is not based on the Tax Object Sales Value (NJOP), but more emphasis on the agreement of the parties, namely the government or the agency which require land with the right to the land.